Membrane desalination : from nanoscale to real world applications - Sapalidis, Andreas (Boca Raton : CRC Press, 2020)
"This book aims to provide details about membrane desalination processes, starting from basic concepts leading to real world implementation. Chapters cover novel research topics such as biomimetic and nanocomposite membranes, nanostructured fillers for mixed matrix membranes, advanced characterization techniques and molecular modelling. Additionally, engineering and economical aspects of desalination as well as the exploitation of green energy sources are also thoroughly presented. This books targets in bridging the gap between the everyday research laboratory practices with practical application demands, so that the readers gain a global perspective of all desalination challenges"--
Introduction to membrane desalination / Andreas A. Sapalidis, Evangelos P. Kouvelos, George E. Romanos, Nick K. Kanellopoulos -- Membrane materials design trends : nano additives / Shadia R. Tewfik, Mohamed H. Sorour, Abdelghani M.G. Abulnour, Hayam F. Shaalan, Heba A. Hani, Marwa M.H. El-Sayed, Yomna O. Abdelrahman, Eman S. Sayed, Aya N. Mohamed, Amany A. Al-Mansoup, Nourhan A. Shawky -- Functionalization routes for the successful incorporation of carbon-based nano-additives into polymeric membranes / Myrsini Kyriaki Antoniou, Andreas A. Sapalidis, Zili Sideratou -- Nanohybrid graphene-based materials for advanced wastewater treatment : adsorption and membrane technology / George Z. Kyzas, Evangelos P. Favvas, Athanasios C. Mitropoulos -- State of the art and perspectives in membranes for membrane distillation/membrane crystallization / Carmen Meringolo, Gianluca Di Profio, Efrem Curcio, Elena Tocci, Enrico Drioli, Enrica Fontananova -- Artificial water channels -- toward next-generation reverse osmosis membranes / Maria Di Vincenzo, Sophie Cerneaux, Istvan Kocsis, Mihail Barboiu -- Introduction to membrane desalination / Rund Abu-Zurayk, Mohammed R. Qtaishat, Abeer Al Bawab -- Molecular modelling of carbon-based membranes for desalination / Georgia Karataraki, Anastasios Gotzias, Elena Tocci -- Virtual material design : a powerful tool for the development of high efficiency porous media / Stephan Barbe and Aron Kneer -- Estimation of process parameters in industrial membrane manufacture using computational fluid dynamics / Stéphan Barbe, Fei Wang, Aron Kneer, Michael Metze, Christian Wenning, Patrick Altschuh, Britta Nestler -- Energy efficiency of reverse osmosis desalination / Mohamed T. Mito and Philip A. Davies -- Membrane fouling and scaling in reverse osmosis / Nirajan Dhakal, Almotasembellah Abushaban, Nasir Mangal, Mohanad Abunada, Jan C. Schippers Maria D. Kennedy -- Sustainable development & future trends in desalination technology / Mattheus Goosen and Hacene Mahmoudi.
OCLC-licensed vendor bibliographic record.
Keywords: Saline water conversion; Membranes (Technology); Nanofiltration; SCIENCE / Chemistry / Industrial & Technical; TECHNOLOGY / Environmental Engineering & Technology